Cytochemical profile of megakaryoblastic leukaemia: a study with cytochemical methods, monoclonal antibodies, and ultrastructural cytochemistry. Issue 6 (June 1987) - Pombo De Oliveira, M S; Gregory, C; Matutes, E; Parreira, A; Catovsky, D
Abstract : A cytochemical study using: Sudan black B; alpha-naphthyl acetate (ANAE) staining; estimation of alpha-naphthyl butyrate (ANBE) esterase activity; acid phosphatase activity; and 5' nucleotidase activity was carried out in 15 cases of megakaryoblastic leukaemia. These included cases of M7 acute myeloid leukaemia and blast crises of chronic granulocytic leukaemia. The megakaryoblastic nature of the blasts was first established using two monoclonal antibodies against platelet glycoproteins, and by estimating the platelet/peroxidase reaction at ultrastructural level. Our findings suggest that megakaryoblasts have a typical cytochemical profile comprising positive ANAE staining and acid phosphatase activity with a predominant localisation in the Golgi zone and negative or weak ANBE activity. A similar positive cytochemical pattern was also found in five cases of erythroleukaemia (M6). The specificity of the 5'nucleotidase activity for megakaryoblasts was not confirmed. In most cases of megakaryoblastic leukaemia there was no 5'nucleotidase activity only two cases showed positive reactions–reactions were positive in several cases of myeloblastic and lymphoblastic leukaemia. We suggest that cytochemical methods may be useful in diagnosing M6 and M7 acute leukaemia because less than 40% of leukaemic cells react with specific monoclonal antibodies.